(untitled) (Research, Society and Development, 2020)
Traffic is a set of complex variables such as vehicle flow and driver behavior, which one variable depends on the other and both depend on the scenario involved. The aim of this study is to analyze the implementation of traffic lights near a roundabout located in the city of Campina Grande-PB, in order to improve the flow and safety of drivers and pedestrians who surround it there. A study was conducted through a questionnaire with drivers and pedestrians using the roundabout daily evaluating the use of traffic lights near the roundabout as a solution to improve the flow in the device, as well as the safety of pedestrians who do crossings in their vicinity. The results of the questionnaire intensify the population’s need to increase the safety and effectiveness of the roundabout at peak times, place of passage of students, workers, UFCG teachers, UEPB teachers, city dwellers who travel daily to work in Campina Grande, among others. Therefore, it is advisable to implement a partial traffic light that operates normally at certain periods of the day and remains with all focus groups flashing in alert form at other times, regularizing vehicle tickets more securely. The traffic light would be activated early in the morning, at lunch time and in the late afternoon, which are peak times, moving the population to their homes and feeding places.